Turner Syndrome Mosaicism 46,Xx/45,X with Graves' Disease: A Case Report - Faisal Rozi Sembiring; Santi Syafril (PP PERKENI, 2025)
Turner syndrome (TS) is a condition in females missing the second sex chromosome (45,X) or parts thereof. It is a rare genetic condition with a wide range of clinical stigmata, such as short stature, delayed puberty and infertility, congenital malformations, and endocrine disorders. TS with chromosomal mosaicism (TSM) is a less severe and less frequent form of TS, who has less pronounced signs and symptoms than the classic TS. A 21-year-old woman with TSM and Graves' disease (GD) is reported. She presented with fatigue, sweating, palpitation, tremor, and the absence of menstruation or breast development. Further investigation reveals diffuse enlargement of thyroid gland and hyperthyroidism symptoms. Laboratory testing shows elevated fT4, low TSH, and elevated TSH receptor antibody levels. Previous chromosomal analysis showed a mosaicism: 46,XX,dup(X) (q28q21.2)[36]/45,X[4]. She is then treated with thiamazole and oral beta-blocker.Discussion: Thyroid abnormalities is common in TS, especially in adult females. This including Hashimoto's thyroiditis and GD. But TS presenting with hyperthyroidism is rare, with most of the cases were reported happens in adult females. Mosaicism in TS resulted in less severe signs and symptoms than the classic TS. Therefore, based on the variabilities, it is often undetected. We reported a rare case of TSM with GD. We observed that mosaicism in this TS patient resulted in less severe GD symptoms, and the response to conventional treatment with thiamazole and oral beta-blocker was satisfactory.